Rapid sample purification approach for 3H determination in seawater using ion exchange resin - Ren, Hong; Ma, Xiaoxiang; Wang, Peng; Yu, Shunfei; Zou, Hua; Cao, Yiyao (Frontiers in Marine Science, 2025)
IntroductionTritium exists in the environment primarily in the form of tritiated water (HTO). There is a significant correlation between the radioactive levels of tritium in seawater and the safety of seafood. By accurately and rapidly detecting the tritium activity concentration in seawater, it is possible to effectively assess its potential impact on the seafood supply chain. At present, the detection of tritium in environmental water samples is often by liquid scintillation counting (LSC). To enable the measure of tritium by LSC, sample purification is necessary, which is commonly performed by distillation. The sample purification by distillation method is somewhat time consuming, especially when processing many samples or large volumes.MethodsTo improve the analytical efficiency in tritium determination, a method for the purification of tritium in seawater using ion exchange resin was developed in this work, which is highly suitable for large-scale environmental monitoring in emergency situations as it significantly shortens the sample processing time (A sample can be purified in 10 min, and multiple samples can be processed simultaneously, which is at least 50 min shorter than the distillation method). The influence of the 90Sr-90Y on the detection of tritium in seawater treated with ion-exchange resin was also discussed. The removal of metal ions from the seawater was achieved using magnetic agitation and filtration by mixing the sample with ion exchange resins.ResultsThe results show that the ion exchange resin can effectively remove metal ions from seawater, and reduce the conductivity of seawater to< 1 μS/cm, and effectively reduce the influence of the 90Sr-90Y on tritium detection. The method was validated using spiked samples and compared with other methods.DiscussionThe recovery of tritium for standard solutions treated by ion exchange method ranged from 85.1% to 98.45%, indicating satisfactory efficiency in sample purification for tritium determination in seawater. 10 seawater samples were collected and used to verify the applicability of the method.